2018
DOI: 10.1159/000494515
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of IL-12Rβ2 and IL-23R Expression on Prognosis of Patients with Laryngeal Cancer

Abstract: Background/Aims: This study aimed to pathologically elucidate the roles of interleukin-12 receptor (IL-12R) β2 and interleukin-23 receptor (IL-23R) expression in tumor cells and tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment and to determine their combined effect on prognosis of laryngeal cancer (LC). Methods: The tumor-cell expression scores and TIL positivity ratiosof IL-12Rβ2 and IL-23R in matched LC and normal laryngeal tissue samples from 61 LC patients were measured via immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…As one example, IL-23 induced the activation of STAT3 in lung cancer cells expressing IL-23R and stimulated their proliferation [77]. The expression of IL-12Rβ2 and IL-23R on laryngeal tumor cells mediated crosstalk between the cancer cells and tumor-infiltrating lymphocytes and affected the prognosis of laryngeal cancer patients [78]. Furthermore, the expression of IL-23R on B-acute lymphoblastic leukemia (B-ALL) cells in B-ALL patients was increased compared to normal B-lymphocytes and acted to upregulate miR15a and downregulate the pro-survival factor BCL2 [79].…”
Section: Il-23 As a Suppressor Of Anti-tumor Immunitymentioning
confidence: 99%
“…As one example, IL-23 induced the activation of STAT3 in lung cancer cells expressing IL-23R and stimulated their proliferation [77]. The expression of IL-12Rβ2 and IL-23R on laryngeal tumor cells mediated crosstalk between the cancer cells and tumor-infiltrating lymphocytes and affected the prognosis of laryngeal cancer patients [78]. Furthermore, the expression of IL-23R on B-acute lymphoblastic leukemia (B-ALL) cells in B-ALL patients was increased compared to normal B-lymphocytes and acted to upregulate miR15a and downregulate the pro-survival factor BCL2 [79].…”
Section: Il-23 As a Suppressor Of Anti-tumor Immunitymentioning
confidence: 99%
“…Tumor-related inflammatory markers have become a focus of many researchers. Previous studies have identified that lymphocyte-to-monocyte ratio, interleukin-12 receptor, immune-inflammatory index and the interleukin-23 receptor can be prognostic indicators for laryngeal cancer ( 12 , 13 ). High neutrophil/lymphocyte level and low lymphocyte level are closely related to tumor invasion and progression ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The IL23R, a member of the IL12 cytokine receptor family, is composed of an IL23R alpha chain and a signaling chain (IL12Rβ1) that is shared with the IL12 receptor (IL12R) ( 12 , 13 ). Although the IL23R−STAT3 pathway is the central element in functional T–helper cell 17 (Th17) development ( 14 , 15 ), expression of the IL23R by tumor-infiltrating Treg has been linked to poor prognosis ( 16 19 ).…”
mentioning
confidence: 99%